2010
DOI: 10.5194/angeo-28-789-2010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic guide field generation in collisionless current sheets

Abstract: Abstract. In thin ( < few λ i ) collisionless current sheets in a space plasma like the magnetospheric tail or magnetopause current layer, magnetic fields can grow from thermal fluctuation level by the action of the non-magnetic Weibel instability (Weibel, 1959). The instability is driven by the counterstreaming electron inflow from the "ion diffusion" (ion inertial Hall) region into the inner current (electron inertial) region after thermalisation by the two-stream instability. Under magnetospheric tail condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…One may ask, for instance in the 22 August 2001 event, why the two flux ropes, 13 min apart, have opposite core field polarities. One possibility is that the seed of the guide field may have changed [e.g., Baumjohann et al, 2010] if the guide field acts as the seed for the core field generation [Karimabadi et al, 1999]. However, we cannot unambiguously determine whether the sign of the guide field changed during the crossings of the two flux ropes.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…One may ask, for instance in the 22 August 2001 event, why the two flux ropes, 13 min apart, have opposite core field polarities. One possibility is that the seed of the guide field may have changed [e.g., Baumjohann et al, 2010] if the guide field acts as the seed for the core field generation [Karimabadi et al, 1999]. However, we cannot unambiguously determine whether the sign of the guide field changed during the crossings of the two flux ropes.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…This suggests some other internal processes in current sheets could also operate in generating and magnifying the B y component. Some theories about the internal processes have been presented, e.g., the plasma pressure anisotropy related with MHD‐equilibrium [e.g., Cowley , 1979], plasma convection [e.g., Hau and Erickson , 1995; Nakamura et al , 2008], or the plasma instability [e.g., Baumjohann et al , 2010] in current sheets. The validity of these theories needs to be verified carefully in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…The Weibel instability has been investigated inside the electron-positron Harris sheet, where structures of the out-of-plane magnetic field are fromed. 29,30 Baumjohann et al 31 studied the structures of the out-of-plane magnetic field inside the electron inertial region in the electron-proton current sheet. They found that the inflow of electrons into the sheet from its two sides may well be capable of selfconsistently generating a weak magnetic guide field via the Weibel instability.…”
Section: Conclusion and Discussionmentioning
confidence: 99%